Q: How much is (2x plus 3y) plus (4x plus y)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)

3x + y

yes

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

Related questions

2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)

4x + 3y - 2x - 7y2x - 4y

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

4x+3y-2x+y 4x-2x+3y+y 2x+4y Taking out 2 common 2(x+2y) Hence the required answer is 2(x+2y)

(2x + 3y)(2x + 5y)

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)

(2x - 3y)(2x - 7y)

4x + 3y = 8x + y so 3y - y = 8x - 4x ie 2y = 4x so y = 2x

4x-2y

3x + y

If you mean: 2x+7y = -1 and 4x-3y = -19 then by substitution x = -4 and y = 1